(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Tepache is a functional fermented beverage made from pineapple by-products. It is rich in prebiotics and bioactive compounds. However, prolonged storage of the beverage can lead to further proliferation of microorganisms, eventually resulting in an undesirable taste and changes in nutritional composition. There is a need to extend the shelf life of the tepache without compromising its organoleptic and nutritional properties. In this study, the effect of high-pressure processing (HPP) on the physicochemical properties, microbial quality, and sensory characteristics of tepache was investigated. Samples were treated at 300, 450, and 600 MPa for 6 min and stored at 4 ℃ for 14 days. Total plate count, pH, total soluble solids, color, DPPH scavenging activity, and sensory evaluation were analyzed. HPP significantly reduced the microbial load, ranging from no viable cells to 6.00 log10 CFU/mL, with 600 MPa showing the highest efficacy. Tepache treated with HPP exhibited higher pH, total soluble solids, and sensory scores, which increased with higher pressure. The treatment maintained the color of the sample, but a slight decrease in b* was observed during storage. The DPPH scavenging activity was improved by the high-pressure treatment, and lower reduction was observed during storage compared to the control sample. The findings suggest that HPP at higher pressure is a suitable option to improve both the shelf life and quality of fermented beverages without compromising their antioxidative properties.